Silver Single‐Atom Catalyst for Efficient Electrochemical CO2 Reduction Synthesized from Thermal Transformation and Surface Reconstruction. Issue 11 (29th January 2021) - Zhang, Ningqiang; Zhang, Xinxin; Tao, Lei; Jiang, Peng; Ye, Chenliang; Lin, Rui; Huang, Zhiwei; Li, Ang; Pang, Dawei; Yan, Han; Wang, Yu; Xu, Peng; et al.
Abstract: We report an Ag1 single‐atom catalyst (Ag1 /MnO2 ), which was synthesized from thermal transformation of Ag nanoparticles (NPs) and surface reconstruction of MnO2 . The evolution process of Ag NPs to single atoms is firstly revealed by various techniques, including in situ ETEM, in situ XRD and DFT calculations. The temperature‐induced surface reconstruction process from the MnO2 (211) to (310) lattice plane is critical to firmly confine the existing surface of Ag single atoms; that is, the thermal treatment and surface reconstruction of MnO2 is the driving force for the formation of single Ag atoms. The as‐obtained Ag1 /MnO2 achieved 95.7 % Faradic efficiency at −0.85 V vs. RHE, and coupled with long‐term stability for electrochemical CO2 reduction reaction (CO2 RR). DFT calculations indicated single Ag sites possessed high electronic density close to Fermi Level and could act exclusively as the active sites in the CO2 RR. As a result, the Ag1 /MnO2 catalyst demonstrated remarkable performance for the CO2 RR, far surpassing the conventional Ag nanosized catalyst (AgNP /MnO2 ) and other reported Ag‐based catalysts. Abstract : Silver nanoparticles converted into single atoms bring about a significant improvement in electrocatalytic CO2 reduction with a 95.7 % faradic efficiency for CO production.